2013
DOI: 10.1161/atvbaha.112.300109
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Biomarkers for the Prediction of Ischemic Stroke

Abstract: Objective-To simultaneously evaluate 14 biomarkers from distinct biological pathways for risk prediction of ischemic stroke, including biomarkers of hemostasis, inflammation, and endothelial activation as well as chemokines and adipocytokines. Methods and Results-The Prospective Epidemiological Study on Myocardial Infarction (PRIME) is a cohort of 9771 healthy men 50 to 59 years of age who were followed up over 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 48 publications
3
53
0
1
Order By: Relevance
“…Not only is resistin positively associated with severity of coronary artery disease and calcification, but can also independently predict major cardiovascular events, including ischemic stroke and cardiovascular mortality. [28][29][30][31] Herein, as expected, we identified a significant and independent association between increased resistin levels and cerebrovascular symptomatology. However, this relationship was observed only among T2DM subjects.…”
Section: Proatherogenic Actions Of Resistinsupporting
confidence: 86%
“…Not only is resistin positively associated with severity of coronary artery disease and calcification, but can also independently predict major cardiovascular events, including ischemic stroke and cardiovascular mortality. [28][29][30][31] Herein, as expected, we identified a significant and independent association between increased resistin levels and cerebrovascular symptomatology. However, this relationship was observed only among T2DM subjects.…”
Section: Proatherogenic Actions Of Resistinsupporting
confidence: 86%
“…Previously, clinical studies have found a negative [9][10][11][12][13][14][15], a positive [16,17], or no association [18][19][20][21][22] between ischaemic stroke and ADP level.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of E-selectin and resistin have shown additive value to traditional risk factors [80]. Plasma glial fibrillary acid protein analysis has shown the ability to differentiate intracranial hemorrhage and ischemic stroke within 4.5 h of symptom onset, and point-of-care systems could be useful in the prehospital phase [81].…”
Section: New Developments and Future Conceptsmentioning
confidence: 99%